Histone Demethylase JmjD2A Regulates Neural Crest Specification - Strobl-Mazzulla, Pablo Hernan (2010)
The neural crest is a multipotent stem cell-like population that is induced during gastrulation, but only acquires its characteristic morphology, migratory ability and gene expression profile after neurulation. This raises the intriguing possibility that precursors are actively maintained by epigenetic influences in a stem cell-like state. Accordingly, we report that dynamic histone modifications are critical for proper temporal control of neural crest gene expression in vivo. The histone demethylase, JumonjiD2A (JmjD2A/KDM4A), is expressed in the forming neural folds. Loss of JmjD2A function causes dramatic down-regulation of neural crest specifier genes analyzed by multiplex NanoString and in situ hybridization. Importantly, in vivo chromatin immunoprecipitation reveals direct stage-specific interactions of JmjD2A with regulatory regions of neural crest genes, and associated temporal modifications in methylation states of lysine residues directly affected by JmjD2A activity. Our findings show that chromatin modifications directly control neural crest genes in vertebrate embryos via modulating histone methylation.